Stepping in the shoes of leaders of populist right-wing parties: promoting anti-immigrant views in times of economic prosperity - Jetten, Jolanda (Social psychology, 2017)
What narrative is deemed most compelling to justify anti-immigrant sentiments when a country’s economy is not a cause for concern? We predicted that flourishing economies constrain the viability of realistic threat arguments. We found support for this prediction in an experiment in which participants were asked to take on the role of speechwriter for a leader with an anti-immigrant message (N = 75). As predicted, a greater percentage of realistic threat arguments and fewer symbolic threat arguments were generated in a condition in which the economy was expected to decline than when it was expected to grow or a baseline condition. Perhaps more interesting, in the economic growth condition, the percentage realistic entitlements and symbolic threat arguments generated were higher than when the economy was declining. We conclude that threat narratives to provide a legitimizing discourse for anti-immigrant sentiments are tailored to the economic context.